2017
DOI: 10.1556/0806.45.2017.030
|View full text |Cite
|
Sign up to set email alerts
|

The effect of foliar spray fertilizers on the tolerance of Hordeum vulgare to UV-B radiation and drought stress

Abstract: The impact of foliar spray fertilizers (Aton Az) on the resistance of spring barley (Hordeum vulgare L.) against to individual and combined UV-B radiation and drought effects were investigated. Barley seeds were sown in pots prepared with neutral pH peat substrate. When the 2 nd true leaf unfolded, i.e. 7 days after germination, the first spray with microelement and free amino acid fertilizers was carried out; two days after this application, the different irradiation (1 and 3 kJm -2 d -1 ) UV-B doses and drou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The results suggested that fertilization was the driving factor in soil CO2 emission dynamics regardless of the physical form of the fertilizer. Januskaitiene and Kaciene [44] showed that foliar fertilization on barley enhanced the photosynthetic rate, leading to an increase in growth and yield as a result of a positive effect on metabolic microbial activity [45]. Solid N fertilizers, from CF and VAN, produced similar cumulative CO2 emissions flux to VFN still encouraging crop development and growth that were higher than the Control.…”
Section: Carbon Dioxide Fluxesmentioning
confidence: 99%
“…The results suggested that fertilization was the driving factor in soil CO2 emission dynamics regardless of the physical form of the fertilizer. Januskaitiene and Kaciene [44] showed that foliar fertilization on barley enhanced the photosynthetic rate, leading to an increase in growth and yield as a result of a positive effect on metabolic microbial activity [45]. Solid N fertilizers, from CF and VAN, produced similar cumulative CO2 emissions flux to VFN still encouraging crop development and growth that were higher than the Control.…”
Section: Carbon Dioxide Fluxesmentioning
confidence: 99%